2002
DOI: 10.1023/a:1019607924403
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Changes Related to CMF Primary Chemotherapy in Breast Cancer

Abstract: The pathologic changes associated to response to primary chemotherapy in a series of 303 operable breast cancers are evaluated and correlated to patients' follow-up (interval free of disease and survival). In our series, the incidence of microscopic changes related to chemotherapy is 43.9%. Tumor replacement by loose fibrosis is the most common pathologic event. In most cases, the intensity of fibrotic change is proportional to the degree of clinical-mammographic reduction of the tumor mass. However, some disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…[5101214] The most common inflammatory host response observed in the present study was lymphocytic; others included mixed inflammation, plasmacytic, prominent histiocytic, and giant cell types. Giant cell reaction was significantly correlated to all types of tumor responses ( P < 0.05).…”
Section: Discussionmentioning
confidence: 93%
“…[5101214] The most common inflammatory host response observed in the present study was lymphocytic; others included mixed inflammation, plasmacytic, prominent histiocytic, and giant cell types. Giant cell reaction was significantly correlated to all types of tumor responses ( P < 0.05).…”
Section: Discussionmentioning
confidence: 93%
“…MTX is used (alone or in combination) to treat both early-stage (as well after surgery and other treatments) and advanced-stage breast cancer. Some selected application of MTX in breast cancer therapy are presented below [196,[213][214][215][216][217][218][219][220][221]244,[265][266][267], Table 2. Martin et al described numerous combination regimens applied in metastatic breast cancer, such as CTX, MTX, 5-FU (CMF), 5-FU, Adriamycin, CTX (FAC) and MTX in combination with tegafur and uracil followed by LV rescue (MUL) [213,214].…”
Section: Methotrexate-based Therapy Of Breast Cancermentioning
confidence: 99%
“…The same research group presented the benefit of application of combination regimen CMF followed by tamoxifen or tamoxifen alone, as adjuvant chemotherapy in women with lymph node-negative breast cancer [266]. Based on experimental data, the authors showed that the classical CMF regimen is safe and plays a key role in the response to therapy in early breast cancer [215,216]. Cocconi et al compared CMF regimen with the modified CMF method they proposed.…”
Section: Methotrexate-based Therapy Of Breast Cancermentioning
confidence: 99%
“…Two additional thresholds have been identified to provide prognostic information in various tumors: response defined by less than 10% of residual viable tumor, and non-response defined by more than 50% residual tumor [7, 9, 14]. Further histopathologic changes following cytotoxic therapy include lymphocytic and histiocytic infiltrates with macrophage activation and subsequent presence of foamy macrophages and giant cells of foreign-body type, and cytopathic changes such as enlargement of tumor cells and the presence of multinucleated giant tumor cells [7, 9, 11, 12, 15, 16]. Nevertheless, there is little information available regarding histopathologic response criteria in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%